Impact Of Investment Motivation, Investment Knowledge And Minimum Investment Capital On Interest In Investing In BPR Buduran Deltapurnama - Ovi Ananda Aulia; Detak Prapanca; Ika Oktaviyanti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This research aims to determine the influence of minimum capital, investment motivation and investment knowledge on customers' interest in investing at Bank BPR Buduran. Quantitative research is included in this type of research. This research uses primary data sources obtained directly from the results of distributing questionnaires via Google Form. The sampling method used was purposive sampling, with the criteria for respondents in this research being customers at BPR banks who were still active members. The number of samples in this research was 84 respondents. The data analysis technique used in this research is multiple linear regression analysis. Data were analyzed using the SPSS version 29 for Windows program. The research results show that: The impact of investment motivation, investment knowledge and minimum investment capital has a positive effect and significantly influences investment interest.